Transfusion-induced HLA antibodies are short-lived and rarely recur post-heart transplantation: a single-center retrospective study with implications for virtual crossmatching - Rajalingam, Raja; Maruthamuthu, Stalinraja; Shy, Brian R.; Cunniffe, Julia; Lowe, David; Aljohani, Othman A.; Wieselthaler, Georg (Frontiers in Immunology, 2026)
IntroductionThe development of human leukocyte antigen (HLA) antibodies poses a major challenge in transplantation by limiting donor compatibility and increasing the risk of graft failure. In patients with advanced heart failure, ventricular assist devices (VADs) are frequently used as a bridge to transplantation and often necessitate perioperative blood transfusions, a recognized trigger for HLA sensitization. However, the risk factors, timing, and clinical relevance of transfusion-induced HLA antibodies in VAD recipients remain incompletely defined.MethodsWe conducted a retrospective analysis of 60 adult heart transplant candidates who underwent VAD implantation and received blood transfusions. HLA antibody profiles were assessed at three time points: pre-VAD implantation, post-VAD/pre-transplantation, and post-transplantation. Patients were categorized according to the number of newly detected HLA antibodies following VAD implantation as non-producers (NP; no new antibodies), low producers (LP; 1–10 antibodies), or high producers (HP; >10 antibodies). Associations between antibody development and demographic characteristics, transfusion exposure, pre-existing sensitization, antibody persistence, and transplant outcomes were evaluated.ResultsFollowing VAD implantation, 73% of patients developed new HLA antibodies, with 65% of these antibodies emerging during the post-VAD/pre-transplant interval. Patient distribution was 35.0% NP, 51.7% LP, and 13.3% HP. Age, ethnicity, and transplant rates were comparable across groups; however, females were disproportionately represented in the HP group (75%, 6 of 8). Neither the number nor the type of blood products transfused was associated with antibody development. The majority of transfusion-associated HLA antibodies were transient, declining rapidly and rarely recurring after transplantation. In contrast, persistent antibodies were predominantly pre-existing and were more frequently observed in female patients, consistent with prior sensitization events such as pregnancy. Notably, unsensitized male patients demonstrated minimal antibody formation following transfusion.DiscussionThese findings indicate that transfusion-induced HLA antibodies in VAD recipients are generally transient and lack durable serologic significance, with little evidence of post-transplant rebound. In contrast, sustained alloimmune responses are primarily driven by pre-existing sensitization, particularly pregnancy-related exposure in female patients. These results support a more individualized approach to HLA antibody surveillance and virtual crossmatching, especially in patients with limited transfusion exposure and no prior sensitization.